Development, implementation and evaluation of nurse-led integrated, person-centred care with long-term conditions. Issue 3 (3rd July 2017) - Harvey, Clare Lynette; Sibley, Jonathan; Palmer, Janine; Phillips, Andrew; Willis, Eileen; Marshall, Robert; Thompson, Shona; Ward, Susanne; Forrest, Rachel; Pearson, Maria
Abstract : Purpose: The purpose of this paper is to outline a conceptual plan for innovative, integrated care designed for people living with long-term conditions (LTCs). Design/methodology/approach: The conceptual plan delivers a partnership between the health system, the person with LTCs (chronic), their family, and the community. The partnership aims to support people at home with access to effective treatment, consistent with the New Zealand Government Health Strategy. This concept of people-owned care is provided by nurses with advanced practice skills, who coordinate care across services, locations and multiple LTCs. Findings: With the global increase in numbers of people with multiple chronic conditions, health services are challenged to deliver good outcomes and experience. This model aims to demonstrate the effective use of healthcare resources by supporting people living with a chronic condition, to increase their self-efficacy and resilience in accordance with personal, cultural and social circumstance. The aim is to have a model of care that is replicable and transferable across a range of health services. Social implications: People living with chronic conditions can be empowered to manage their health and well-being, whilst having access to nurse-led care appropriate to individual needs. Originality/value: Although there are examples of case management and nurse-led coordination, this model is novel in that it combines a liaison nursing role that works in partnership with patients, whilst ensuring that care across a number of primary and secondary care services is truly integrated and not simply interfaced.